(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
According to World Health Organization, health is a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity. In Ayurveda also, health is nothing but harmonious balance in Doshas, Dhatus, Malas as well as Agni alongside a pleasant state of Atma, Manas and Indriya. Food and lifestyle plays important role in maintenance of health. Out of which food is most important factor for sustenance of healthy life and ensuring physiological function in human body. Food is not only essential for our physical wellbeing but it also nourishes mind. Digestion and assimilation of food is immensely important otherwise it can lead to diseases of gastrointestinal tract. Ajeerna means indigestion which is the first biomarker of malfunctioning of Jathaaragni. According to Charak Samhita, weak state of Jathaaragni (Agnimandya) is the root cause of all disease. Similarly, Madhav nidan also has mentioned that if Ajeerna is left untreated can lead to many diseases. So process of Ajeerna must be blocked by following the correct diet according to an individual’s Prakriti and with proper medication treatment and lifestyle modifications. For the prevention of Ajeerna, Acharya Charak has mentioned dietary rules in the form of Ashtau ahar Vidhi Vishesh Ayatana and Acharya Shushrut has mentioned Dashvidha Ahara Vidhi vidhan. By following these guidelines and making thoughtful adjustments to diet and lifestyle, individuals can prevent the onset of Ajeerna and related diseases, ensuring the maintenance of balanced Agni and overall health.